Temporal changes within mechanical dyssynchrony and rotational mechanics in Takotsubo syndrome: A cardiovascular magnetic resonance imaging study. (15th December 2018) - Backhaus, Sören J.; Stiermaier, Thomas; Lange, Torben; Chiribiri, Amedeo; Lamata, Pablo; Uhlig, Johannes; Kowallick, Johannes T.; Raaz, Uwe; Villa, Adriana; Lotz, Joachim; Hasenfuß, Gerd; Thiele, Holger; et al.
Abstract: Background: The pathophysiological significance of dyssynchrony and rotation in Takotsubo syndrome (TTS) is unknown. We aimed to define the influence of cardiovascular magnetic resonance feature tracking (CMR-FT) dyssynchrony and rotational mechanics in acute and during clinical course of TTS. Methods: This multicenter study included 152 TTS patients undergoing CMR (mean 3 days after symptom onset). Apical, midventricular and basal short axis views were analysed in a core-laboratory. Systolic torsion, diastolic recoil and dyssynchrony expressed as circumferential and radial uniformity ratio estimates (CURE and RURE: 0 to 1; 1 = perfect synchrony) were compared to a matched control group (n = 21). Follow-up CMR (n = 20 patients; mean 62 days, SD 7.2) and general follow-up (n = 136; mean 3.3 years, SD 2.4) were performed. Results: CURE was initially reduced compared to controls (p = 0.001) and recovered at follow-up (p < 0.001) as opposed to RURE (p = 0.116 and p = 0.179). CURE and RURE discriminated between ballooning patterns (p = 0.001 and p = 0.045). Recoil was generally impaired during the acute phase (p = 0.015), torsion only in highly dyssynchronous patients (p = 0.024). Diabetes (p = 0.007), physical triggers (p = 0.013) and malignancies (p = 0.001) predicted mortality. The latter showed a distinct association with impaired torsion (p = 0.042) and dyssynchrony (p = 0.047). Physical triggers and malignancies were related to biventricular impairment (p = 0.004 and p = 0.026), showing higher dyssynchrony (p < 0.01), greater reduction of left ventricular function (p < 0.001) and a strong trend towards increased mortality (p = 0.074). Conclusion: Transient circumferential dyssynchrony and impaired rotational mechanics are distinct features of TTS with different severities according to the pattern of ballooning. Patients with malignancies and precipitating physical triggers frequently show biventricular affection, greater dyssynchrony and high mortality risk. Highlights: Transient circumferential dyssynchrony is a distinct feature of acute TTS. Recoil is impaired in the acute phase, whilst torsion remains preserved. High amounts of dyssynchrony are associated with additionally impaired torsion. Precipitating physical triggers are related to biventricular impairment.